A intersetorialidade e a estratégia saúde da família: desafios da relação entre o discurso e a prática - Ana Maria Ribeiro de Almeida (2008)
Introduction: The Family Health Estrategy ESF, established by the Ministry of Health as a strategy for reorganizing Primary Health Care and reorienting the health care model is based on the Health Promotion paradigm; and intersectorality is a tool used to enable resolutive action against determinants in the health/illness process. This presupposition, though consolidated in discourse, has still not been consolidated in practice. Objectives: The aim of this research is to address the intersectorality theme and its relation to Family Health discourse and practice. We examined Family Health performance in the municipality ofDivinópolis, MG, regarding intersectoral issues, based on actors perception, in an attempt to identify challenging or facilitating factors throughout the strategy implementation process. Methodological Strategy: First, we reviewed the literature on the theme of intersectorality and its interfaces with the health field and Family Health practice; then, we carried out a case study, adopting a qualitative approach and multiple methodological procedures and sources of evidence: self-reporting questionnaires, focus groups, interviews, and document analysis.Data was analyzed according to the hermeneutic-dialectic method. Results: A review of the literature points to synergy between the Family Health framework and health promotion. It also reveals a close relation between primary health care, health promotion and intersectorality, in addition to the latters importance to the development of democracy andenhanced citizenship awareness. The results of the case study highlight several problems constituting obstacles to the effective practice of intersectorality and these are related to human resources, municipal management and social participation. Conclusion: Intersectorality both depends on and influences change of the health care model, permanenteducation being an indispensable factor in the process. Municipal management and Family Health professionals performance may be considered key items for effective social empowerment and intersectorality, the last two being key issues in re-orienting the health care model, enhancing the democratic process and fostering greater social equity.